An Updated View on an Emerging Target: Selected Papers from the 8th International Conference on Protein Kinase CK2 - Lorenzo A. Pinna (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The 8th International Conference on Protein Kinase CK2 (www.uks.eu/ck2), organized by Matthias Montenarh and Claudia Götz, will be held at the Faculty of Medicine of Saarland University, in Homburg, Germany, from 6-9 September, 2016. Protein kinase CK2 is a serine/threonine kinase, which is highly conserved in evolution. Knock-out experiments have shown that this enzyme is absolutely necessary for cell viability. The enzyme is highly expressed in rapidly proliferating cells, which goes along with an elevated enzyme activity. Protein kinase CK2 is involved in a broad range of signaling pathways, regulating proliferation, differentiation, apoptosis, or senescence. Recent advances towards the characterization of the three-dimensional structure of protein kinase CK2 and its subunits will undoubtedly yield important new insights into its regulation, and the functions of CK2. Moreover, with two inhibitors of the enzyme presently in clinical phase II trials, human protein kinase CK2 has appeared as an emerging target for cancer diseases.